A study on factors influencing repeat purchase, positive word of mouth and consumer satisfaction in the luxury car industry. - Chan, Adrian Yan Ren. (2008)
This study examines the influence of product quality, service quality, brand love, and brand image-self-concept congruence on repeat purchase, positive word of mouth and customer satisfaction in the Singapore luxury car industry. Two hundred and ten respondents completed self-administered questionnaires. Results suggested that only brand love had a significant influence on all three dependent variables, while service and product quality affected only consumer satisfaction. Brand image-actual self congruence was shown to influence both repeat purchase and positive word of mouth, and it was also found to be effective in moderating the relationship between brand image-desired self congruence and repeat purchase. Our study suggests that marketing communications should try to match product brand image to consumer self concept and instil brand love to ensure continued success.